2022
DOI: 10.1177/14614448211063621
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the community: How digital media promotes safer behavior during the Covid-19 pandemic in authoritarian communities—a case study of the ultra-Orthodox community in Israel

Abstract: The Covid-19 pandemic has ushered in new behaviors and digital practices. This study explores how digital media has advanced safer behavior among ultra-Orthodox Israeli adults during the pandemic in authoritarian societies. We explored the level of adherence to government-issued health guidelines during the Covid-19 pandemic by conducting a public opinion survey among a representative sample of ultra-Orthodox Israeli adults ( N = 500) during the second Covid-19 wave (Autumn 2020). The results show that digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…For example, U.S. college students had high levels of anxiety and stress caused by the pandemic but used different types of media to enhance their well-being (Eden et al 2020). Among ultra-Orthodox Israeli adults, digital media use (i.e., websites, apps, and social media) encouraged adherence to health safety protocols, such as mask-wearing, social distancing, and hygiene (Shomron and David 2022). Interestingly, these behaviors occurred among adults who used digital and social media for educational or essential purposes (e.g., online banking).…”
Section: Mediating Influence Of Religiosity and Spirituality On Subje...mentioning
confidence: 99%
“…For example, U.S. college students had high levels of anxiety and stress caused by the pandemic but used different types of media to enhance their well-being (Eden et al 2020). Among ultra-Orthodox Israeli adults, digital media use (i.e., websites, apps, and social media) encouraged adherence to health safety protocols, such as mask-wearing, social distancing, and hygiene (Shomron and David 2022). Interestingly, these behaviors occurred among adults who used digital and social media for educational or essential purposes (e.g., online banking).…”
Section: Mediating Influence Of Religiosity and Spirituality On Subje...mentioning
confidence: 99%
“…For example, during the COVID-19 outbreak in Israel, it was suggested that targeted interventions by the government could improve compliance with physical distancing measures among the Arab population [ 30 ]. In a similar manner, Shomron and David [ 31 ] stated that responsible risk communication through digital channels and adaptation to cultural media habits helped promote safer behavior during times of emergency for the ultra-orthodox Israeli communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although COVID‐19 was considered a focal point in the relations between the Israeli government and its constituents, regarding information and communication (Yavetz et al, 2022), this was not unchartered territory for the emergency authorities (Shomron & David, 2022). Israel has faced multiple emergencies and crises situations since its inception.…”
Section: Literature Reviewmentioning
confidence: 99%